CONTEXTUAL STUDY OF FAMILY LAW: RETHINKING DIFFERENTIAL ROLES AND POSITIONS OF WOMEN (INDONESIAN COUNCIL OF ULAMA/MUI) IN KEDIRI CITY FAMILIES IN THE PANDEMIC ERA - Siti Aminah; Siti Sumadiyah (Jurnal Pembaharuan Hukum, 2021)
This research is an effort to affirm the role and position of women in the family who are no longer on the sub-ordinate line. By carrying out a contextual study based on the rules of fiqh legal provisions depend on the god who follows and taghayyur, al-ahkam bi taghayyur al-azminah wa al-amkinah, the research has a significant point. To ensure the validity of this research, the research data is a scientific research method that can be accounted for. The data is extracted through the triangulation method, namely interviews, observation and documentation. The data results were tested for the validity of the data through triangulation of sources and techniques. After the final data, the findings of the study were obtained. Namely, 1) on the economic aspect of the family, women work in a community by developing micro-enterprises; 2) in the social aspect, women provide counselling, socialisation, both online and offline; 3) in the spiritual aspect, women carry out halaqah on family resilience during the pandemic and socialise the MUI fatwa related to vaccination law; 4) in the education aspect, women provide services, education and education to the wider community in dealing with the Covid-19 pandemic.